INTERNATIONAL LEGAL STANDARDS OF HUMAN RIGHTS: TOWARDS THE OBJECTIVITY OF THE ISSUE OF CODIFICATION WORKS - Mykhailo O. Baimuratov; Boris Ya. Kofman; Natalia V. Yefremova (Alfred Nobel University Journal of Law)
The article is devoted to the identification, definition and research of theoretical and praxeological factors and trends leading to the objectification of the issue of codification works in the field of international legal standards of human rights. It is proved that issue of human and citizen rights and freedoms, since the creation of the UN in 1945, has been a fundamental object of cooperation between states in the modern international community (see the Preamble to the 1945 UN Charter). That is why at the level of such an association of modern states, as well as at the regional and bilateral levels, in order to detail and specify the mandatory obligations of states in this most important sphere of interaction, a large number of multilateral and bilateral international interstate treaties, which, firstly, affect a wide range of subjects (people, women, children, disabled people, believers, prisoners, soldiers, prisoners of war, the elderly, pensioners, athletes, etc.), and secondly, establish mandatory obligations of their member states (international legal obligations of states, obligations of states under international treaties signed by them) in relation to a wide range of rights recognized by their legally recognized international catalog (personal, political, economic, social, cultural, environmental), thirdly, in the process of their implementation in various conditions (peacetime, state of martial law or war, environmental and man-made disasters, other extraordinary conditions of existence and functioning of statehood, etc.). It is noted that in the modern world, since the creation of the UN, the protection and observance of the basic rights and freedoms of a person and a citizen have ceased to be the competence of a specific country, but have become the business of the entire international community, since, first of all, it is the "alpha and omega" of international cooperation of states in its boundaries (the teleological factor of the modern international order – author); secondly, it is precisely within its limits that a powerful international legal array of treaty law documents was created regarding such specialized protection and protection of human and citizen rights / thanks to the increased concern and attention of the international community to these issues at various times, authoritative international organizations, including the UN, adopted about 300 declarations, conventions, charters/ (determining source factor of the modern international order – author); thirdly, for a long time, they have been the most important task of many states of the world community in terms of fulfilling their international legal obligations, taken within the framework of the international treaties signed by them and the implementation of their instructions within the limits of national jurisdiction (a mandatory factor of the modern international order – author); fourthly, there are clear international legal mechanisms of protection, protection and control over the fulfillment by member states of the international community of international legal obligations in the field of human and citizen rights and freedoms (the technologically protected factor of international protection, protection and control of modern international order – author); fifthly, the regulatory and technological phenomenon "international legal standards of the rights and freedoms of man and citizen" was used for the first time, which was transformed into an important, modern, effective phenomenology of modern international law, based on the relevant international and national implementation mechanisms of the international treaty law and provides for the mandatory borrowing of the above standards by the national constitutional legislation of the states – respectively, either signatories, or participants, or parties to relevant contractual international legal acts (transformational and implementation factor of international protection, protection and control of the modern international order – author). It is argued that, taking into account the special importance and socio-legal significance of international legal standards of human and citizen rights and freedoms for the formation and implementation of institutional-organizational and regulatory-obligatory guidelines of the modern international legal order, based on the fundamental principles of public international law, the problem of their codification acquires of significant importance.